Sonication protocols and their contributions to the microbiological diagnosis of implant-associated infections: a review of the current scenario - Silva, Natally Dos Santos; De Melo, Beatriz Souza Toscano; Oliva, Alessandra; de Araújo, Paulo Sérgio Ramos (Frontiers in Cellular and Infection Microbiology, 2024)
Addressing the existing problem in the microbiological diagnosis of infections associated with implants and the current debate about the real power of precision of sonicated fluid culture (SFC), the objective of this review is to describe the methodology and analyze and compare the results obtained in current studies on the subject. Furthermore, the present study also discusses and suggests the best parameters for performing sonication. A search was carried out for recent studies in the literature (2019-2023) that addressed this research topic. As a result, different sonication protocols were adopted in the studies analyzed, as expected, and consequently, there was significant variability between the results obtained regarding the sensitivity and specificity of the technique in relation to the traditional culture method (periprosthetic tissue culture – PTC). Coagulase-negative Staphylococcus (CoNS) and Staphylococcus aureus were identified as the main etiological agents by SFC and PTC, with SFC being important for the identification of pathogens of low virulence that are difficult to detect. Compared to chemical biofilm displacement methods, EDTA and DTT, SFC also produced variable results. In this context, this review provided an overview of the most current scenarios on the topic and theoretical support to improve sonication performance, especially with regard to sensitivity and specificity, by scoring the best parameters from various aspects, including sample collection, storage conditions, cultivation methods, microorganism identification techniques (both phenotypic and molecular) and the cutoff point for colony forming unit (CFU) counts. This study demonstrated the need for standardization of the technique and provided a theoretical basis for a sonication protocol that aims to achieve the highest levels of sensitivity and specificity for the reliable microbiological diagnosis of infections associated with implants and prosthetic devices, such as prosthetic joint infections (PJIs). However, practical application and additional complementary studies are still needed.